Plantar pressure experienced during tennis specific movements performed on the 3 grand slam court surfaces - Strauss, D. N.; Messenger, N.; Utley, A.; Brooks, P.; Miller, S. (ESM 2008 emed scientific meeting, 2008)
Recent epidemiological studies report the general increase in prevalence of lower limb injuries in tennis (Strauss, 2003; Cassell, 1999; Bylak 1998). In part this finding is not entirely unexpected as worldwide participation in tennis continues to grow (LTA, 2007; Francesom, 2005; Cassell 1999) it would therefore be expected that injury levels rise in accordance. However, the rise in lower limb injuries appears disproportionate to other regions. It has long been established that impact force is at the centre of injury generation (Nigg, 1986). Strauss (2007) identified typical impact forces produced during tennis specific movements will range from 2.44BW to 2.80BW. This is related to movement velocity and is significantly dependent on the hardness of the playing court surface, with acrylic courts eliciting the maximum impact forces. The distribution of these impact forces about the foot is largely unknown. The aims of this study are (1) to identify typical plantar pressures experienced during tennis specific movements and (2) in vivo assessment of the affect of a change in court surface in relation to the peak pressures experienced